Volunteers [videorecording (DVD)] - Meyer, Nicholas, 1945-; Hanks, Tom; Candy, John; Wilson, Rita (HBO Home Video, 1999)
A young man escapes the bookies he owes $28,000 by fleeing to Thailand with a group of Peace Corps volunteers.